2009
DOI: 10.1016/j.intimp.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain treatment reduces CD25 expression on activated CD4+ T cells in vitro

Abstract: Bromelain (Br), an extract from pineapple stem with cysteine protease activity, exerts anti-inflammatory effects in a number of inflammatory models. We have previously shown that Br treatment decreased activated CD4+ T cells and has a therapeutic role in an ovalbumin-induced murine model of allergic airway disease. The current study was designed to determine the effect of Br on CD4+ T cell activation, specifically the expression of CD25 in vitro. CD25 is up regulated upon T cell activation, found as a soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
1
27
0
5
Order By: Relevance
“…Due to its proteolytic activity, bromelain has been extensively used in therapeutic applications in several animal models (Ahle 1987;Bahde 2007;Bhui et al 2009). A wide range of therapeutic benefits have been attributed to bromelain due to its action as therapeutic target in inflammation, autoimmunity and allergy, as well as the reversible inhibition of platelet aggregation, bronchitis relief, improved recovery after surgical traumas, and enhanced absorption of drugs, particularly of antibiotics (Kelly 1996;Murakawa 2002;Roep 2002;Secor 2009). Enzymatic debridement of necrotic tissues from ulcers, burn wounds and frostbite eschar as well as anti-proliferative and anti-metastatic effects in tumor models have been also studied (Ahle 1987;Napper et al 1994;Bhui et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its proteolytic activity, bromelain has been extensively used in therapeutic applications in several animal models (Ahle 1987;Bahde 2007;Bhui et al 2009). A wide range of therapeutic benefits have been attributed to bromelain due to its action as therapeutic target in inflammation, autoimmunity and allergy, as well as the reversible inhibition of platelet aggregation, bronchitis relief, improved recovery after surgical traumas, and enhanced absorption of drugs, particularly of antibiotics (Kelly 1996;Murakawa 2002;Roep 2002;Secor 2009). Enzymatic debridement of necrotic tissues from ulcers, burn wounds and frostbite eschar as well as anti-proliferative and anti-metastatic effects in tumor models have been also studied (Ahle 1987;Napper et al 1994;Bhui et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following the stimulation, the activation maker such as CD25 can be upregulated. As the high affinity alpha chain of IL-2 receptor, the binding of CD25 to the IL-2 can trigger a cascade response, resulting in T cell proliferation and additional IL-2 production [16]. IL-2 is also defined as a Th1 cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…secreted by activated T helper cells or a higher Th1/Th2 ratio in various of immune overwhelming diseases, such as autoimmune, allergy and transplantation rejection [17][18][19]. Therapeutic interventions to such diseases are often designed to reduce the threshold of T cell activation [16]. Therefore, immnosuppressive drugs, like cyclosporine A (CsA) and dexamethasone (Dex), are often used in these immune overwhelming diseases [20,21] In the present study, we found that icaritin at a quite low concentration could act as an immunosuppressant to reduce T cell proliferation, IL-2/CD25 expression, and Th1 cytokines production in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In a study using peripheral blood mononuclear cells (PBMC), Bromelain decreases the expression of migration/activation related cell surface markers on leukocyte by proteolysis, including CD14, CD16, CD21, CD25, CD44, CD45RA, CD62L [263]. In addition, it can dosedependently reduce CD25 expression in anti-CD3 antibody-stimulated CD4 + T cells, which is upregulated when T cells are activated in inflammation, autoimmunity and allergy [264].…”
Section: Bromelainmentioning
confidence: 99%